PEMANFAATAN PENGINDERAAN JAUH UNTUK ESTIMASI STOK KARBON DI AREA REKLAMASI PT. ANTAM UBPE PONGKOR, KABUPATEN BOGOR - Andini Tribuana Tunggadewi; Lailan Syaufina; Nining Puspaningsih (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Mining is an environment-altering activity especially on land by reducing landcover and stored carbon. PT ANTAM, a prominent mining company in an industrial scale, is doing reclamation in order to restore the ability of the land to its optimum function. Reclamation in the relation with global warming, is an efforts to mitigate climate change by increasing the ability of land to absorb carbon (revegetation). Therefore land cover monitoring at reclamation area becomes an important thing to do, one way to do it is by using remote sensing. Not only for land cover, remote sensing also can be used to estimate carbon stocks. Based on visual interpretation of google earth image data in 2007, there were five classes of secondary forest at reclamation area of PT ANTAM UBPE Pongkor : class A (tight forest) covering 8,65 ha; class B (medium forest) covering 0,88 ha; class C (sparse forest) covering 1,57 ha; and class D (shrubs) covering 0,92 ha. Meanwhile, the calculation of carbon stocks based on three sampling locations that representing secondary forest classes A, B, and C, resulting estimated average carbon stock in the whole reclamation area of PT ANTAM UBPE Pongkor is 113,79 tons/ha. Keywords: mining, reclamation, google earth image data, carbon stock